Bevacizumab for NF2‐associated vestibular schwannomas of childhood and adolescence. Issue 5 (2nd March 2020) - Renzi, Samuele; Michaeli, Orli; Salvador, Hector; Alderete, Daniel; Ponce, Nicolas Fernandez; Zapotocky, Michal; Hansford, Jordan R.; Malalasekera, Vajiranee S.; Toledano, Helen; Maguire, Bryan; Bouffet, Eric; Ramaswamy, Vijay; et al.
Abstract: Seventeen children at six institutions with neurofibromatosis type 2 (NF2)‐related vestibular schwannomas received bevacizumab. Eight of the 13 patients with initial hearing loss (61%) showed objective hearing improvement within six months of treatment. No patients showed hearing deterioration during therapy; however, only two patients showed objective radiological response. Seven of eight patients had tumor progression or worsening hearing loss upon cessation of treatment. Bevacizumab was well tolerated with no patients discontinuing therapy. Bevacizumab appears to postpone hearing loss in childhood NF2‐associated vestibular schwannomas, but responses are not durable, suggesting that either longer maintenance therapy or new strategies are required.